If it's not what You are looking for type in the equation solver your own equation and let us solve it.
14p-6=22+20p
We move all terms to the left:
14p-6-(22+20p)=0
We add all the numbers together, and all the variables
14p-(20p+22)-6=0
We get rid of parentheses
14p-20p-22-6=0
We add all the numbers together, and all the variables
-6p-28=0
We move all terms containing p to the left, all other terms to the right
-6p=28
p=28/-6
p=-4+2/3
| *46+x÷6−21=25+6 | | 8x-8=2(6x+8 | | 3=n+8/5 | | 3(x-3)-12=2(x-6)-10 | | 5x+10=64 | | 10x-22=342 | | y/8+4=13 | | v÷5−4=31 | | -n-3-5n=-15 | | -6=p/15-5 | | 4(3x-1)+x=35 | | 3/3=x/9 | | 9x-7=6x+9-2 | | 15m+0.50m=25+0.25m | | r+9/5=5 | | 7+.20p=5+.0.30p | | 7+.20p=5+.0.30 | | -9–7p=9–10p | | 122x+64=2x-100 | | -0.75w-1=11 | | 4.4(-2w-7.4=-62.48 | | 3/4(x-48)=12 | | 600x=2x | | 4x-78=180 | | 28=-9a+1 | | 2(n+1)+3(n-2)=21 | | 8(3s+2)=304 | | 3=x/3.33 | | 5n-9n-2=-14 | | 7r+10=-4+9r | | 1y+8=9 | | 6^x=216 |